2014
DOI: 10.1016/j.ijgo.2014.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Poor uptake of influenza vaccination in pregnancy in northern India

Abstract: Influenza vaccination among pregnant women in northern India is nonexistent. Poor uptake is rooted in misperceptions about vaccine availability, efficacy, and safety among treating physicians, few of whom are vaccinated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
3
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 24 publications
3
29
3
1
Order By: Relevance
“…One of the most commonly provided reasons by the unvaccinated was that their doctor had not discussed during their pregnancy. The finding that more than one third of those unvaccinated did not receive a health care provider recommendation is in line with previous studies [34, 36, 41, 43, 44]. Another commonly provided reason was the concern that vaccination may not be safe during pregnancy.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…One of the most commonly provided reasons by the unvaccinated was that their doctor had not discussed during their pregnancy. The finding that more than one third of those unvaccinated did not receive a health care provider recommendation is in line with previous studies [34, 36, 41, 43, 44]. Another commonly provided reason was the concern that vaccination may not be safe during pregnancy.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it is important to design and to implement interventions in order to increase the vaccination rate. The value observed in the present study is higher than those reported in other countries, since no women had received influenza vaccination in the already mentioned study in India [34], 3% in Turkey [36], 4% in Thailand [26], and it is almost identical to the 6% in Iran [37], 10.9% in Germany [38], and 16% in Canada [39]. Whereas, it is substantially below the levels observed in Australia with an uptake of 27% [20], in France of 39% [40], in Belgium of 42.8% [41], and in the United States with levels ranging from 35% [14] to 66.4% [42].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In India, influenza vaccine uptake among pregnant women is extremely poor (12.8% for pandemic influenza vaccine and none for seasonal influenza) [30, 31]. The lack of disease burden data among pregnant Indian women may have contributed to the perception that prevention of influenza in pregnant women and young children may not be a public health priority.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2004, the ACIP and the American College of Obstetricians and Gynecologists (ACOG) have recommended influenza vaccination for all women of Americas who are or will be pregnant regardless of trimester of pregnancy [44,45]. In India, Federation of Obstetric and Gynaecological Societies of India (FOGSI) have recommended Influenza vaccination for mothers from 26 weeks onwards [46].…”
Section: Immunogenicity and Efficacy Of A Rough Brucella Suis Vaccinementioning
confidence: 99%